Influence of IOL Weight on Long-Term IOL Stability in Highly Myopic Eyes - Chen, Yuxi; Meng, Jiaqi; Cheng, Kaiwen; Lu, Qiang; Wei, Ling; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2022)
Purpose: To investigate the influence of IOL weight on long-term IOL stability in highly myopic eyes. Materials and Methods: Totally, 205 highly myopic cataract eyes of 205 patients implanted with the MC X11 ASP (Group A, 86 eyes) or 920H IOL (Group B, 119 eyes) were included in the retrospective study. Eyes were divided into 3 subgroups according to the IOL power: low (≥ -5 to < 5 D), medium (≥ 5 to < 14 D), and high (≥ 14 D) IOL power. At 3 years after surgery, IOL decentration and tilt, high-order aberrations, and anterior capsular opening (ACO) area were measured. The influence of IOL weight on long-term IOL stability was evaluated. Results: Group B had significantly greater IOL weight than Group A (P < 0.001). Correspondingly, Group B presented significantly greater overall and inferior decentration than Group A, especially for low and medium IOL power (all P < 0.05). In both groups, overall and vertical decentration was significantly correlated with IOL weight (all P < 0.05). Group B showed significantly greater ACO area than Group A (P < 0.05). Multivariate analysis showed that decentration in Group A was affected by IOL weight, while decentration in Group B was affected by IOL weight and AL. Conclusions: Higher IOL weight may lead to greater long-term IOL decentration in highly myopic eyes, while haptic design may play a role on anterior capsular contraction.